2010
DOI: 10.1037/a0018982
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of guided self-help treatment for recurrent binge eating.

Abstract: Objective-Adoption of effective treatments for recurrent binge-eating disorders depends on the balance of costs and benefits. Using data from a recent randomized controlled trial, we conducted an incremental cost-effectiveness analysis (CEA) of a cognitive behavioral therapy guided self-help intervention (CBT-GSH) to treat recurrent binge eating compared to treatment as usual (TAU).Method-Participants were 123 adult members of an HMO (mean age = 37.2, 91.9% female, 96.7% non-Hispanic White) who met criteria fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
88
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 73 publications
6
88
0
1
Order By: Relevance
“…In summary, this study replicated and extended the findings from our earlier study (23), which demonstrated that a CBT-GSH intervention could significantly improve clinical outcomes for binge eating in a highly cost-effective manner (39). The study reported here provides further evidence that effective care for binge eating is possible in real-world settings.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In summary, this study replicated and extended the findings from our earlier study (23), which demonstrated that a CBT-GSH intervention could significantly improve clinical outcomes for binge eating in a highly cost-effective manner (39). The study reported here provides further evidence that effective care for binge eating is possible in real-world settings.…”
Section: Discussionsupporting
confidence: 83%
“…This study was a replication and extension trial of our original study examining the effectiveness and cost-effectiveness of a brief guided self-help treatment for binge eating disorders in a nonspecialty health care (HMO) setting (23,39). Despite several changes to recruitment, assessment, and target population to reflect how such a program might be utilized in everyday practice conditions, the results pattern was similar to what we found in the earlier study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings corroborate prior findings from cost-effectiveness analyses of (guided) bibliotherapy for depression (Smit et al, 2006;Vos, Corry, Haby, Carter, & Andrews, 2005) and binge-eating disorder (Lynch et al, 2010), although these interventions were based on cognitive behavioral therapy (CBT). Economic evaluations of web-based self-help interventions (mostly CBT-based) for mental health are more abundant (Donker et al, 2015).…”
Section: Discussionsupporting
confidence: 81%
“…En distintos estudios la modalidad de autoayuda de la tcc no solo ha obtenido resultados similares a la tip y superiores a otros tratamientos -como la terapia de conducta de pérdida de peso-, sino que ha resultado ser más efectiva en costes que el tratamiento habitual, tal como demostraron Lynch et al (2010) empleando el método cea (Cost-Effective Analysis).…”
Section: Eficacia Comparativa De Los Distintos Tratamientos Para El Taunclassified